THE SYNERGY OF TAX DIGITALIZATION IN ENHACING TAX COMPLIANCE - Richard Andrew; Lusy; Stanislaus Adnanto Mastan; Yosef Pranata (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes This study examines how digitalization, tax understanding, and technology-based socialization influence MSME taxpayer compliance.The research focuses on MSMEs in Surabaya and Sidoarjo, East Java—regions with the third-largest MSME populations in Indonesia, totaling over 1.2 million businesses. Sidoarjo hosts approximately 206,000 MSMEs, while Surabaya has 65,000. Both regions serve as major industrial hubs in East Java. Research Method Using a purposive sampling method, data were collected through a structured questionnaire distributed via Google Forms, employing a 5-point Likert scale. This quantitative study aims to analyse whether the increasing level of digitization and technology-driven tax initiatives can sustain MSME taxpayer compliance amid the rapid advancements of the Industrial Revolution 5.0. Research Results and Findings The study emphasizes the importance of taxpayer education and the effectiveness of digital tax systems in fostering long-term compliance among MSMEs, contributing to the broader discourse on sustainable tax practices in a digital economy.